2006
DOI: 10.1111/j.1475-097x.2006.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood flow and autonomic function in full‐term infants

Abstract: The results of the present study in agreement with previous studies reflect the vulnerability of infants in prone position as related to brainstem function. However, it appears that ABFV and autonomic functions as reflected by HRV are independent physiological measures, possibly indicating regulation autonomy of the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
(88 reference statements)
2
7
0
Order By: Relevance
“…We did not find any correlation between gender and either parameter of the HRV which is in accordance with the findings of Javorka et al and Yanget al [26,38].. On the other hand, Nagy et al found significantly lower HR and lower HRV, expressed as the standard deviation of the HR, in boys [39]. Male newborns had a significantly decreased pNN50 (namely HF) compared to females when lying prone [32].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We did not find any correlation between gender and either parameter of the HRV which is in accordance with the findings of Javorka et al and Yanget al [26,38].. On the other hand, Nagy et al found significantly lower HR and lower HRV, expressed as the standard deviation of the HR, in boys [39]. Male newborns had a significantly decreased pNN50 (namely HF) compared to females when lying prone [32].…”
Section: Discussionsupporting
confidence: 91%
“…Since LF spectrum is supposed to reflect the sympathetic activity [26], we can assume that the cardiac sympathetic modulation is less pronounced in prone position. Similarly, Gabai et al found reduced HRV parameters analysed in time domain in three-day old term newborns in a prone position [32]. In prone position, they showed a decrease in SDNN (standard deviation of normal R-R) which correlated with TP and also a decrease in short term variability (assessed by pNN50) which correlated with HF.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, impaired cerebral blood flow (CBF) may be an important contributor. Previous studies have revealed blood flow to be impaired through the internal jugular vein 39 and the vertebral and basilar arteries 40,41 of infants in the prone position with their heads turned to the side. Furthermore, in preterm infants these prone-related deficits in vertebral artery flow were found to be maximal at 1 month CA compared with the newborn period, 42 suggesting position-dependent changes in CBF may be aggravated with advancing age.…”
Section: Effects Of Sleep Positionmentioning
confidence: 99%
“…found significantly lower HR and lower HRV, expressed as the standard deviation of the HR, in boys [39]. Male newborns had a significantly decreased pNN50 (namely HF) compared to females when lying prone [32].…”
Section: Discussionmentioning
confidence: 83%